Caracterización del servicio de alojamiento y hospedaje en el municipio de Duitama, como herramienta de desarrollo del sector turístico. (2023)
This proposal seeks to characterize the accommodation and lodging service in the municipality of Duitama as a tool to create a statistical base that allows the development of the tourism sector. For the execution of the project, four phases designed for the research are taken into account.